Human cadavers Vs. multimedia simulation: A study of student learning in anatomy. Issue 5 (10th January 2014) - Saltarelli, Andrew J.; Roseth, Cary J.; Saltarelli, William A.
<x xml:space="preserve">Abstract</x> Multimedia and simulation programs are increasingly being used for anatomy instruction, yet it remains unclear how learning with these technologies compares with learning with actual human cadavers. Using a multilevel, quasi‐experimental‐control design, this study compared the effects of "Anatomy and Physiology Revealed" (APR) multimedia learning system with a traditional undergraduate human cadaver laboratory. APR is a model‐based multimedia simulation tool that uses high‐resolution pictures to construct a prosected cadaver. APR also provides animations showing the function of specific anatomical structures. Results showed that the human cadaver laboratory offered a significant advantage over the multimedia simulation program on cadaver‐based measures of identification and explanatory knowledge. These findings reinforce concerns that incorporating multimedia simulation into anatomy instruction requires careful alignment between learning tasks and performance measures. Findings also imply that additional pedagogical strategies are needed to support transfer from simulated to real‐world application of anatomical knowledge. Anat Sci Educ 7: 331–339. © 2014 American Association of Anatomists.